Mathematical modeling of ER-positive breast cancer treatment with AZD9496 and palbociclib - Wei, Hsiu-Chuan (AIMS mathematics, 2020)
Breast cancer is a heterogeneous disease. Understanding the tumor subtypes can help identify the best option of treatment. Mathematical modeling of tumor growth is a useful tool to understand the observed clinical phenomena. This work is based on a previously published mathematical model of breast cancer in MCF-7 cell line. In this paper, cancer therapy using AZD9496 and palbociclib is incorporated into the mathematical model. Numerical results produced using the mathematical model are compared with those observed in clinical and experimental studies. Numerical simulation shows that monotherapy with AZD9496 can inhibit the growth of a tumor with a restricted tumor size, monotherapy with palbociclib is ineffective, and combination therapy with AZD9496 and palbociclib can produce synergistic effect and control a larger tumor.